Anxiety and Affect in Psychoanalysis - Malcolm Macmillan (Jesuit University Ignatianum in Krakow, 2010)
I examine the concept of affect or emotion in psychoanalysis in the context of Freud's theory of anxiety especially that of the mechanism he proposed for inhibiting the psychological and physiological responses when anxiety-provoking situations threatened to recur.  Freud pictures the original and subsequent experiences of anxiety as catastrophic and their recurrences as equally damaging.  I argue that his picture and the deficiencies in the control mechanism he proposed have resulted in a lack of attention being given intense emotions in the psychoanalytic literature and a complete failure to consider those of less intensity.